How Do We Teach Social Justice? A Cross-Disciplinary Synthesis of Social Justice Andragogy - Das, Bagmi; Farrell, Isabel; Vashisht, Kriti; Gantt, Alexandra; Simpson, Elisabeth; Johnson, Adrianne (International Journal of Multicultural Education, 2023)
Social Justice is a critical component of many of the helping disciplines. Similar goals govern these different disciplines, which are reflected in the scholarship of their professional training. However, the crossover in scholarship is limited. This review of social justice andragogy literature from various fields in the United States creates a conversation among these helping disciplines so that they may be able to learn from each other. From these separate realms of scholarship, the authors have derived terms and recommendations of what these disciplines may learn from one another through their shared obstacles and through processing of their work.